The aqueduct, Fréjus, France. Line engraving by G. Hackert a - Auteur inconnu (Wikimedia Commons)
Notice iconographique issue de Wikimedia Commons. Titre: The aqueduct, Fréjus, France. Line engraving by G. Hackert a. The aqueduct, Fréjus, France. Line engraving by G. Hackert after J.P. Hackert, 1778. Iconographic Collections Keywords: Jacob-Abraham Hackert | Georg-Abraham Hackert
Licence Creative Commons Attribution 4.0 via Wikimedia Commons
Keywords: iconographie; illustration; gravure; Patrimoine; Wikimedia Commons